HOW PARTICIPATION SHAPES LOCAL DEVELOPMENT - Muhadjir Darwin (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2016)
This article elaborates citizens’ participation in shaping local development in the Indonesian context. The main question is how to make local development more participatory as a guarantee that citizens’ rights are fully realized. In that respects, social accountability is a key that should be improved from supply and demand sides simultaneously. From the supply side, there is a need to reform local governance, in order to improve the quality of local regulations, local planning, local budgeting, and local public service provision. While from the demand side, there is a need to empower local citizens so that they are engaged in five forms or local development efforts: local regulation formulation, local development planning, local budgeting, community driven development, and public service provision.